Pengaruh Kemudahan Transaksi dan Kepercayaan Pengguna terhadap Kepuasan Pengguna Fitur Shopee Paylater E-Commerce Shopee - Khasanah, Kholifatul; Aswad, Muhammad (Jurnal Dinamika Ekonomi dan Bisnis, 2024)
The shift in people's attitude towards a completely digital system has prompted a rise in online shopping on different e-commerce platforms. Therefore, innovations have arisen from businesses in the electronic commerce industry, including the introduction of credit payment options. Shopee needs to create consumer satisfaction by implementing effective strategies, such as maximizing the use of their credit payment method called "Shopee Paylater," in order to stay competitive with other businesses. When customers are fully satisfied, they are more likely to continue using credit payment services on e-commerce platforms and also share positive recommendations with others. Satisfaction can also lead to a decrease in negative complaints regarding an e-commerce company. This research aims at examining the effect of the ease of transactions and the users trust on user satisfaction of the Shopee Paylater feature on Shopee E-Commerce. The research had a sample size of 75 participants. The method of purposive sampling was used to make a determination. The chosen analytic tool is IBM SPSS 22, which employs the techniques of multiple linear regression analysis. This study discovered that the ease of transaction had a positive and significant effect on user satisfaction. Similarly, user trust had a positive and significant effect on user satisfaction. Additionally, both ease of transactions and user trust had a combined influence on user satisfaction